No evidence for allelic association of a human CTLA-4 promoter polymorphism with autoimmune thyroid disease in either population-based case-control or family-based studies. - Heward, J; Allahabadia, A; Carr-Smith, J; Daykin, J; Cockram, C; Gordon, C; Barnett, A; Franklyn, J; Gough, S (1998)
OBJECTIVE: The cytotoxic T lymphocyte associated-4 (CTLA-4) gene is a candidate for T-cell mediated autoimmune disease and polymorphism has been reported to be associated with both type 1 diabetes and autoimmune thyroid disease. A previously unreported polymorphism of the promoter region of the human CTLA-4 gene has recently been described in a sample of a normal control population. We investigated the distribution of this polymorphism, situated at position -318 to the ATG start codon and resulting in a C-T change leading to an Mse I restriction site, in both population based case control studies and family studies in patients with Graves' disease (Caucasian and Hong Kong Chinese), autoimmune hypothyroidism and systemic lupus erythematosus (SLE). DESIGN: Target DNA was amplified using the polymerase chain reaction and the resulting product was digested using the Mse I restriction enzyme. PATIENTS: One hundred and ninety-one white UK Caucasian and 98 Hong Kong Chinese patients with Graves' disease, 78 white UK Caucasian patients with Graves' disease plus family members, 92 white UK Caucasian patients with autoimmune hypothyroidism, 13 white UK Caucasian patients with autoimmune hypothyroidism plus family members, 132 white UK Caucasian patients with systemic lupus erythematosus, 355 white UK Caucasian control subjects and 82 Hong Kong Chinese control subjects. MEASUREMENTS: Frequencies of the C and T alleles were compared between patients and control subjects using the chi 2-test and Fisher's exact test for small numbers. RESULTS: No association with the T allele was observed in any of the patient groups studied. CONCLUSION: These data suggest that the C-T change in exon 1 of the promoter region of the CTLA-4 gene does not play a role, nor is in linkage disequilibrium with a disease causing mutation, in the development of autoimmune disease.